(untitled) (ModaPalavra e-periódico, 2016)
The present article presents partial results of a Ph. D. research, developed through a partnership among FAU-USP, Universitàt Politecnica de València and UEL, which purpose is the study of a fashion design methodological instrumental bringing up tools that are destined to facilitate the formal syntax of wearable artifacts, within the project of teaching. In this way, this explanation reports a snip of the exploratory research. Arranging the academic practice bibliographic closing and document analysis, it defines the construct guiding of a didactic approach to the use of methodological tools of design. The results reinforce the hypothesis that a good project reasoning is built on the platform of “significant learning”, of knowledge management systemic models and of synthesis methods.